Chemometrical exploration of combinatorially generated drug-like space of 6-fluoroquinolone analogs - Minovski, Nikola (Acta chimica slovenica, 2010)
A classical virtual combinatorial chemistry approach (CombiChem) was applied for combinatorial generation of 5590 novel structurally-similar 6-fluoroquinolone analogs by using a virtual synthetic pathway with selected primary (43) and secondary amines (130). The obtained virtual combinatoriallibrary was filtered using an in-house developed set of cheminformatics drug-likeness filters with pre-integrated Boolean options (TRUE/FALSE) for compounds reductionlselection. The retained number (304) of fluoroquinolone analogs (with TRUE outcome) defines the drug-like chemical space (CombiData). Quantitative structure-activity relationships (QSAR) study on these 304 virtually generated 6-fluoroquinolone analogs with unknown activity values was performed using a pre-built five-parameter multiple linearregression (MLR) model developed on a set of compounds with experimentally determined activity values (R" = 0.8417, R".cv= 0.7884). The obtained activity values for the unknown compounds together with the model results were used to define the applicability domain (AD). The obtainedAD offers a good graphical representation and establishment of structure-activityrelationships (SAR) which could be used for design of new 6-fluoroquinolones with possible better activity.
Keywords: chemistry; farmacija; fluorokinoloni; kemija; pharmacy; tuberkuloza